Perlindungan Hukum Konsumen yang Mengkonsumsi Obat Tradisional Produksi Industri Mengandung Bahan Kimia Obat Berbahaya - Sri Hardhina Kunjayanti; Agus Widodo (Prosiding Seminar Nasional Ilmu Hukum, 2024)
Medicinal chemicals (BKO) are chemical compounds that are commonly added to traditional medicinal preparations to increase the drug's indications and offer a powerful and rapid impact in illness treatment. Traditional medicines containing BKO in Indonesia, particularly in East and West Java, are increasing year after year, from 43 to 50-53 traditional remedies containing medicinal compounds. Using the normative method, researchers will be able to use the findings of empirical legal science and other sciences to analyze and explain law without altering the character of normative legal science. The Consumer Protection Law Number 8 of 1999 regulates legal protection for consumers who consume industrially produced traditional medicines containing dangerous chemical chemicals. Article 19 (1) states that business actors are responsible for compensating consumers for damage, pollution, and/or losses caused by the consumption of goods and/or services produced or traded. (2) The compensation described in paragraph (1) may take the form of a refund or replacement of products and/or services of the same kind or equivalent value, or health care, and/or the payment of compensation in line with the provisions of the applicable laws and regulations. (3) Compensation is granted within 7 days after the transaction date. (4) Providing compensation as stated in paragraphs (1) and (2) does not preclude criminal prosecution based on further evidence indicating the presence of an element of error. (5) If the business actor can demonstrate that the error was caused by the customer, the rules intended in paragraphs (1) and (2) do not apply. Suggestions for effective implementation. Suggestions so that they can be implemented well.